Purification, gene cloning, and characterization of γ-butyrobetainyl CoA synthetase from Agrobacterium sp. 525a*. Issue 8 (2nd August 2016) - Fujimitsu, Hiroshi; Matsumoto, Akira; Takubo, Sayaka; Fukui, Akiko; Okada, Kazuma; Mohamed Ahmed, Isam A.; Arima, Jiro; Mori, Nobuhiro
Abstract : The report is the first of purification, overproduction, and characterization of a unique γ-butyrobetainyl CoA synthetase from soil-isolated Agrobacterium sp. 525a. The primary structure of the enzyme shares 70–95% identity with those of ATP-dependent microbial acyl-CoA synthetases of the Rhizobiaceae family. As distinctive characteristics of the enzyme of this study, ADP was released in the catalytic reaction process, whereas many acyl CoA synthetases are annotated as an AMP-forming enzyme. The apparent K m values for γ-butyrobetaine, CoA, and ATP were, respectively, 0.69, 0.02, and 0.24 mM. Graphical abstract: γ-Butyrobetainyl CoA synthetase, the first enzyme of the β-oxidation-like pathway involving γ-butyrobetaine degradation, was reported in this study.